Let’s join the toy inventors: designing an inclusive collaborative play toy with and for autistic children - Mohamad Hassan Fadi Hijab (17862620) (2025)
Engaging autistic children in collaborative activities offers unique opportunities, especially when creating tools that facilitate social interaction while accommodating their diverse needs. Through a three-phase co-design process involving both autistic and non-autistic children, the study explores engagement levels, sensory preferences, and communication dynamics during the development of a collaborative play prototype. Additionally, it explored how children played with the resulting co-designed prototype. The study involved nine autistic and four non-autistic children, aged 7–12, recruited from two locations in Qatar. The findings revealed that autistic children initially preferred solitary play, with low levels of engagement. However, as they progressed through the structured activities in the co-design phases, the autistic children gradually transitioned towards collaborative play. The study also demonstrated diverse sensory preferences among the children and highlighted the importance of non-verbal communication in facilitating collaboration. Overall, the study showcased the effectiveness of structured co-design activities in fostering social interaction among autistic children and emphasised the importance of adaptable design techniques to accommodate diverse sensory and communication needs. Other Information Published in: CoDesign License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/15710882.2025.2468445